ANALISIS KECERDASAN EMOSIONAL DALAM PEMBELAJARAN AKUNTANSI KEUANGAN SISWA KELAS XI SMKN 3 PONTIANAK - Andriany, Mendy; Ulfah, Maria; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the emotional intelligence of students in learning financial accounting in Ak 2 class SMKN 3 Pontianak. This research is based on the finding of a problem when the authors make observations about the emotional intelligence of students when learning financial accounting. The research method used is descriptive method with a qualitative approach and survey research forms. The source of data in this study is the students of class XI AK 2, amounting to 38 students. Data collection is obtained through observation guidelines and interview guidelines, then analysis using data reduction, data presentation, and verification / conclusion drawing based on students' affective success based on comparison of numbers (percentages) and predicates, then checking the validity of the data using technical trigulations. The author conducts research by conducting research observations 2 times and interviewing 1 time. The results show that recognizing one's emotions (self-awareness) can be stated to be unfavorable, managing emotions (self-regulation) and motivating yourself can be declared not good, recognizing the emotions of others (empathy) expressed otherwise, and building relationships (social skills) can be expressed sufficiently well.Â Keywords: Recognizing Self Emotions, Managing Emotions, MotivatingÂ Yourself, Recognize the Emotions of Others, Build RelationshipsÂ